Prevalence and Characteristics of Ceftriaxone-Resistant Salmonella in Children’s Hospital in Hangzhou, China - Shi, Qiucheng; Ye, Yihua; Lan, Peng; Han, Xinhong; Quan, Jingjing; Zhou, Mingming; Yu, Yunsong; Jiang, Yan (Frontiers in Microbiology, 2021)
The non-Typhi Salmonella (NTS) infection is critical to children’s health, and the ceftriaxone is the important empirical treatment choice. With the increase resistance rate of ceftriaxone in Salmonella, the molecular epidemiology and resistance mechanism of ceftriaxone-resistant Salmonella needs to be studied. From July 2019 to July 2020, a total of 205 NTS isolates were collected, 195 of which (95.1%) were cultured from stool, but 10 isolates were isolated from an extraintestinal site. Serogroup B accounted for the vast majority (137/205) among the isolates. Fifty-three isolates were resistant to ceftriaxone, and 50 were isolated from children younger than 4years of age. The resistance rates for ceftriaxone, ciprofloxacin, and levofloxacin were significantly higher in younger children than the older children. The resistance genes in the ceftriaxone-susceptible isolates were detected by PCR, and ceftriaxone-resistant Salmonella were selected for further whole-genome sequencing. Whole-genome analysis showed that serotype Typhimurium and its monophasic variant was the most prevalent in ceftriaxone-resistant isolates (37/53), which comprised ST34 (33/53), ST19 (2/53), and ST99 (2/53), and they were close related in the phylogenetic tree. However, the other isolates were diverse, which included one Enteritidis (ST11), one Indiana (ST17), one Derby (ST40), four Kentucky (ST198), two Goldcoast (ST2529, ST358), one Muenster (ST321), one Virchow (ST359), one Rissen (ST469), one Kedougou (ST1543), two Uganda (ST684), and one Kottbus (ST8839). Moreover, CTX-M-55 ESBLs production (33/53) was found to be mainly responsible for ceftriaxone resistance, followed by blaCTX-M-65 (12/53), blaCTX-M-14 (4/53), blaCTX-M-9 (2/53), blaCTX-M-64 (1/53), blaCTX-M-130 (1/53), and blaCMY-2 (1/53). ISEcp1, IS903B, IS Kpn26, IS1F, and IS26 were connected to antimicrobial resistance genes transfer. In conclusion, the dissemination of ESBL-producing Salmonella isolates resulted in an increased prevalence of ceftriaxone resistance in young children. The high rate of multidrug resistance should be given additional attention.